Psychedelic-induced mystical experiences: An interdisciplinary discussion and critique - Mosurinjohn, Sharday; Roseman, Leor; Girn, Manesh (Frontiers in Psychiatry, 2023)
Contemporary research on serotonergic psychedelic compounds has been rife with references to so-called ‘mystical’ subjective effects. Several psychometric assessments have been used to assess such effects, and clinical studies have found quantitative associations between ‘mystical experiences’ and positive mental health outcomes. The nascent study of psychedelic-induced mystical experiences, however, has only minimally intersected with relevant contemporary scholarship from disciplines within the social sciences and humanities, such as religious studies and anthropology. Viewed from the perspective of these disciplines - which feature rich historical and cultural literatures on mysticism, religion, and related topics - ‘mysticism’ as used in psychedelic research is fraught with limitations and intrinsic biases that are seldom acknowledged. Most notably, existing operationalizations of mystical experiences in psychedelic science fail to historicize the concept and therefore fail to acknowledge its perennialist and specifically Christian bias. Here, we trace the historical genesis of the mystical in psychedelic research in order to illuminate such biases, and also offer suggestions toward more nuanced and culturally-sensitive operationalizations of this phenomenon. In addition, we argue for the value of, and outline, complementary ‘non-mystical’ approaches to understanding putative mystical-type phenomena that may help facilitate empirical investigation and create linkages to existing neuro-psychological constructs. It is our hope that the present paper helps build interdisciplinary bridges that motivate fruitful paths toward stronger theoretical and empirical approaches in the study of psychedelic-induced mystical experiences.